2004
DOI: 10.1002/eji.200324174
|View full text |Cite
|
Sign up to set email alerts
|

Monomethylfumarate affects polarization of monocyte‐derived dendritic cells resulting in down‐regulated Th1 lymphocyte responses

Abstract: Psoriasis vulgaris, a type-1 cytokine-mediated chronic skin disease, can be treated successfully with fumaric acid esters (FAE). Beneficial effects of this medication coincided with decreased production of IFN-+ . Since dendritic cells (DC) regulate the differentiation of T helper (Th) cells, this study focussed on effects of monomethylfumarate (MMF, bioactive metabolite of FAE) on polarization of monocyte-derived DC. MMF-incubated, lipopolysaccharide-stimulated DC (MMF-DC) produced dramatically (p X 0.05) red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 30 publications
0
66
0
1
Order By: Relevance
“…Keratinocytes play an active role in the production of inflammatory mediators (cytokines and chemokines) in the psoriatic cytokine network (Steinhoff et al, 2001;Gröne, 2002;Nestle et al, 2009). Accordingly, we hypothesized that MMF exerts a unique anti-inflammatory action by inhibiting major inflammatory mediators produced not only by immune cells (Litjens et al, 2004b) but also by keratinocytes. We opted to examine the effect of MMF on the expression of TNFa, IL-1a, and IL-6 in keratinocytes treated with TPA, which is known to activate keratinocytes and induce inflammatory mediator release (Kim et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Keratinocytes play an active role in the production of inflammatory mediators (cytokines and chemokines) in the psoriatic cytokine network (Steinhoff et al, 2001;Gröne, 2002;Nestle et al, 2009). Accordingly, we hypothesized that MMF exerts a unique anti-inflammatory action by inhibiting major inflammatory mediators produced not only by immune cells (Litjens et al, 2004b) but also by keratinocytes. We opted to examine the effect of MMF on the expression of TNFa, IL-1a, and IL-6 in keratinocytes treated with TPA, which is known to activate keratinocytes and induce inflammatory mediator release (Kim et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Data have been published regarding the effects of FAEs (including MMF) on endothelial as well as immune cells; however, little is known about their effects on keratinocytes (Nibbering et al, 1993;Thio et al, 1994;Litjens et al, 2004b;Wallbrecht et al, 2011;Dehmel et al, 2014). Thus, MMF has known effects on immune cells, such as dendritic cells and granulocytes, which could possibly account in part for its antipsoriatic actions (Nibbering et al, 1993;Litjens et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that MMF can increase IL-4, an anti-inflammatory interleukin, or can decrease IFN-γ, an inflammatory factor. These effects can reduce inflammatory responses (13,29).…”
Section: Introductionmentioning
confidence: 99%
“…Other early phase reactions involving the modulation of important proinflammatory enzymes such as cyclooxygenase 1 and 2, 69 together with the synthesis and release of prostaglandin E2 70 and histamine, 71 are also reported to be affected by Lymphomyosot's components, as are immune system molecules that can play critical roles in early stages of an immune system response, the dendritic cells. 72 Furthermore, the regulation of leukocyte infiltration by macrophages 73 at least partly by influencing the expression of macrophage migration inhibitory factor 74 and the activity of important adhesion molecules 38,75 such as vascular cell adhesion protein 1 (VCAM-1) and intracellular adhesion molecule 1 (ICAM-1) seem to be regulated by certain components of Lymphomyosot. Finally, Lymphomyosot also helps modulate the synthesis and release of nitric oxide.…”
mentioning
confidence: 99%